Informal recycling, income generation and risk: Health and social harms among people who use drugs - Jaffe, Kaitlyn (Int J Drug Policy, 2018)
BACKGROUND: Informal recycling refers to the street-based collection of discarded materials for reuse, resale, or return to a recycling facility for money. While qualitative research has explored experiences and perceptions of informal recycling, little is known about the scope and exposures associated with informal recycling among people who use drugs (PWUD). METHODS: Using data from two prospective longitudinal cohorts of PWUD, we examined the prevalence of informal recycling and its association with social, structural and health risks, including criminal justice system involvement. RESULTS: Between June 2010 and May 2015, of 1664 participants, 557 (33.5%) reported engaging in informal recycling during the study period. In multivariable generalised estimating equations (GEE) analyses, informal recycling was positively associated with injection drug use (Adjusted Odds Ratio (AOR)=1.43, 95% Confidence Interval (CI) 1.21–1.68), public injection (AOR=1.27, 95% CI 1.09–1.49), methamphetamine use (AOR=1.35, 95% CI 1.05–1.72), difficulty finding harm reduction equipment (AOR=1.16, 95% CI 1.02–1.32), and police interactions (AOR=1.35, 95% CI 1.18–1.55). Sub-analyses revealed PWUD engaged in informal recycling were more likely to be told to move on, ticketed, stopped for jaywalking, and directed to services by police. CONCLUSIONS: These findings suggest informal recycling as a situated practice for PWUD, with potential indications for higher-risk drug use, experiencing greater surveillance and difficulty accessing health and addiction treatment services. This research highlights the significance of the broader risk environment and the need for health-promoting policies for socioeconomically marginalised PWUD engaged in informal recycling.